Gambaran Komponen Senyum Pasien Sebelum Perawatan Ortodonti (Kajian Foto Frontal di Klinik Ortodonti RSGMP FKG UI) - Yuri Analia; Nia Ayu Ismaniati; Maria Purbiati (Faculty of Dentistry, Universitas Indonesia, 2013)
Smile is a non-verbal communication to express spontaneous feelings and emotions. Most patients that come to have orthodontic treatments want to have an attractive smile, but before the treatment smile has not yet been studied. There are eight components to make ideal frontal smile: lip line, smile arc, upper lip curve, buccal corridor, symmetry of smile, occlusal plane, dental and gingival components. This study was descriptive in design, in order to obtain frontal smile description before orthodontic treatment of RSGMP FKG UI patients that were grouped according to facial form, age, and gender. The results of the study show that patient smile before orthodontic treatment frequently exhibits medium lip line and the mean of incisor display at 75% of clinical crown. Most subjects show gingival display of 2 mm or less. On the smile arc, the most common features are straight smile and consonant smile. Equally common smile arc positions are those touching and not touching lower lip. The average buccal corridor is in medium smile, and thus most subjects have straight upper lip curves and symmetric smiles. DOI: 10.14693/jdi.v15i1.80